Strengthening Risk Communication in Disaster Management Based Religion and Local Wisdom in North Sumatra - Husni, Muhammad; Sazali, Hasan (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2025)
North Sumatra is a region with a high level of disaster vulnerability, particularly the eruption of Mount Sinabung and flash floods in Langkat. The government's risk communication remains technocratic and one-way, making it less suited to the community's perspective, which is heavily influenced by religious values and local wisdom. Consequently, some residents rely more on natural signs, kinship networks, and the authority of religious figures in responding to disaster threats. This situation highlights the importance of integrating cultural and spiritual values into mitigation strategies. This study aims to analyze the forms of risk communication occurring in the community, identify relevant religious values and local wisdom, and formulate strategies to strengthen risk communication based on the local context. A qualitative case study approach was used in Karo and Langkat Regencies through in-depth interviews, observation, and documentation, which were then analyzed using an interactive analysis model. The results indicate that risk communication occurs through three channels: formal government channels, culture-based communication, and religious communication. Values such as mutual cooperation, traditional taboos, natural signs, and religious moral messages strengthen information acceptance and enhance community preparedness. This research implies the need for an integrative risk communication model involving religious leaders, traditional leaders, and the government to build more effective and sustainable disaster resilience.